Perancangan Dokumen Analisis Risiko dan Audit Internal pada Sistem Manajemen Mutu ISO 9001:2015 di PT. X - Priskila Nathania Devi; Jani Rahardjo (Jurnal Titra, 2022)
PT. X already has ISO 9001:2015 certification, but there are several deficiencies in the required documents, such as risk analysis document and internal audit activity has not been carried out. This research is focused on designing risk analysis, audit checklist questions, internal audit procedures, management review procedures and corrective action procedures. Risk analysis is made in all Minibus Production Departments at PT. X using the Failure Mode Effect Analysis (FMEA), Fishbone Diagram, and Five Why Analysis methods, while the audit checklist design is made in the form of a list of questions that will be compared with the requirements in the ISO 9001:2015. The results of risk identification show that the percentage of the highest number of risk factors as a whole is the method factor, which is 64%, followed by the man factor at 24%, the machine factor at 12% and the material, measure, and environmental factors each at 0%. The design of the internal audit is carried out by making an audit checklist and internal audit procedures that are useful for preparing the company to carry out the internal audit process.